Physicochemical Composition and Apparent Degree of Polymerization of Fructans in Five Wild Agave Varieties: Potential Industrial Use - Pamela I. Aldrete-Herrera; Mercedes G. López; Luis Medina-Torres; Juan A. Ragazzo-Sánchez; Montserrat Calderón-Santoyo; Marisela González-Ávila; Rosa I. Ortiz-Basurto (Foods, 2019)
In this study, we characterize fructan extracts from five wild agave varieties at three ages to identify their potential use in the food industry. Physicochemical parameters (solids soluble total and pH), sugar content and fructan distribution profiles by high-performance anion-exchange chromatography (HPAEC) were evaluated. We found that the ages and variety influenced the carbohydrate content and also fructan dispersion. Two- to four-year-old plants exhibited the highest concentrations of free sugars and fructans, with a low apparent degree of polymerization (DPa) of ≤9 monomers, which highlights their potential use as prebiotics. Conversely, 10- to 12-year-old plants presented a low concentration of free sugars and fructans with a maximum DPa of 70 monomers, which can be used to obtain fractions with high, intermediate and low DPa. These fractions have a potential use in the food industry as prebiotic, soluble fibers, stabilizers and sweeteners, among others. The agave varieties Agave spp., Agave salmiana, and Agave atrovirens showed mainly fructooligosaccharides (FOSs). Due to the presence of these low molecular carbohydrates, prebiotics, fermented products and/or syrups could be obtained. A. salmiana spp. crassipina and Agave tequilana variety cenizo presented DPa ≤50 and DPa ≤70, respectively, which could be useful in the production of fructan fractions of different DPa. These fractions might be used as functional ingredients in the manufacture of a wide range of food products.